Luminal STIM1 Mutants that Cause Tubular Aggregate Myopathy Promote Autophagic Processes - Sallinger, Matthias; Tiffner, Adéla; Schmidt, Tony; Bonhenry, Daniel; Waldherr, Linda; Frischauf, Irene; Lunz, Victoria; Derler, Isabella; Schober, Romana; Schindl, Rainer (International journal of molecular sciences, 2020)
Stromal interaction molecule 1 (STIM1) is a ubiquitously expressed Ca2+ sensor protein that induces permeation of Orai Ca2+ channels upon endoplasmic reticulum Ca2+-store depletion. A drop in luminal Ca2+ causes partial unfolding of the N-terminal STIM1 domains and thus initial STIM1 activation. We compared the STIM1 structure upon Ca2+ depletion from our molecular dynamics (MD) simulations with a recent 2D NMR structure. Simulation- and structure-based results showed unfolding of two α-helices in the canonical and in the non-canonical EF-hand. Further, we structurally and functionally evaluated mutations in the non-canonical EF-hand that have been shown to cause tubular aggregate myopathy. We found these mutations to cause full constitutive activation of Ca2+-release-activated Ca2+ currents (ICRAC) and to promote autophagic processes. Specifically, heterologously expressed STIM1 mutations in the non-canonical EF-hand promoted translocation of the autophagy transcription factors microphthalmia-associated transcription factor (MITF) and transcription factor EB (TFEB) into the nucleus. These STIM1 mutations additionally stimulated an enhanced production of autophagosomes. In summary, mutations in STIM1 that cause structural unfolding promoted Ca2+ down-stream activation of autophagic processes.
Keywords: kationty dvojmocné; nádorové proteiny; rozbalení proteinů; autofagie; Calcium; simulace molekulární dynamiky; mutace; Ca2+; vápník; Stromal Interaction Molecule 1; motivy EF-ruky; Molecular Dynamics Simulation; Cations, Divalent; EF-hand; konformace proteinů, alfa-helix; protein STIM1; TFEB; STIM; EF Hand Motifs; MITF; Autophagy; lidé; Humans; Myopathies, Structural, Congenital; Protein Conformation, alpha-Helical; SOCE; hydrophobic pocket; Neoplasm Proteins; myopatie strukturální vrozené; Mutation; Orai; tubular aggregate myopathy; Protein Unfolding